Die Bundesrepublik Deutschland und die Türkei 1978 bis 1983 - Szatkowski, Tim 1976- (Zeitgeschichte im Gespräch, 2016)
"Based on German Foreign Office records, now fully assessed for the first time, Tim Szatkowski shows the interests pursued by the German federal government in its policy toward Turkey between 1978 and 1983. The study reveals that after the military coup in Ankara, Germany could not reconcile Realpolitik and human rights, and this resulted in major strains in German-Turkish relations due to policies regarding asylum and foreigners."--Provided by publisher